Hubungan antara Komunikasi Ibu dan Anak, Pola Asuh Orang Tua, dan Sumber Informasi dengan Kesiapan Menghadapi Menarche pada Remaja Awal - Nur Hanifah, Diyah Risnanda; Dewi, Mustika; Sariati, Yuseva (-)
Menarche is the first menstruation in women which indicates the maturity of a healthy women and not pregnant. The first menstruation occurs at the age of 10-13 years, even in some children occurs faster so that children need to be prepared early to face menarche. There are at least 24% students from 75 students who are not ready to face menarche. This unpreparedness can cause feelings of fear and confusion in the face of menarche. This study aims to find out whether there is a relationship between mother and child communication, parenting style, and sources of information with preparation for facing menarche in early adolescents. This study uses an observational analytic design with cross sectional approach. The sample used was adolescents aged 10-12 years in SD Negeri Model Kota Malang who lived with mothers and had not experienced menarche. Data collection using questionnaire sheets and analyzed using chi square test. The results of chi square analysis of communication variables mother and child obtained p value = 0.00, parenting styles variables obtained value p = 0.444, and information source variables obtained p value = 0.144. The conclusion of this study is that there is a relationship between mother and child communication with readiness to face menarche in early adolescents and there is no relationship between parenting styles and the number of sources of information with readiness to face menarche in early adolescents.